Aspects of the biology of Campbell Island feral sheep (Ovis aries L.) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Zoology at Massey University - Ballance, Alison (Massey University, 1986)
The feral sheep population of Campbell Island was studied between April and August 1984. Data were collected from 2529 of the 4000 sheep killed in the south-east of the island, and the population described. Productivity and timing of lambing are examined. A survivorship curve and the age:sex characteristics are plotted to illustrate mortality and population structure. Changes in population size and lambing rates since 1895 are presented. Attributes such as wool colour, occurrence of horns, body size and lambing dates are described. In several respects these differed significantly between localities, and the existence of distinct sub-populations is suggested. The presence of these sub-populations is related to home range behaviour. Observations were made of 70 tagged sheep in the area around Menhir during April-June 1984, and it is suggested that they adhere to a home range, the mean size of which was 43.3 ha. Sheep were found associated in groups of up to 65, although mean size was 6.31. There was no constancy in group composition, although several hogget:dam associations were noted. Groups comprised both rams and ewes. Time activity observations showed that in winter the sheep spent 70.2% of the time grazing, and 16.6% ruminating, with ruminating peaking around midday.
Keywords: New Zealand Campbell Island; Feral livestock; Sheep